Tensile overload-induced texture effects on the fatigue resistance of a CoCrFeMnNi high-entropy alloy. (15th February 2023) - Lam, Tu-Ngoc; Chin, Hsu-Huan; Zhang, Xiaodan; Feng, Rui; Wang, Huamiao; Chiang, Ching-Yu; Lee, Soo Yeol; Kawasaki, Takuro; Harjo, Stefanus; Liaw, Peter K.; Yeh, An-Chou; Chung, Tsai-Fu; et al.
Abstract: The present study investigates the crystallographic-texture effects on the improved fatigue resistance in the CoCrFeMnNi high-entropy alloys (HEAs) with the full-size geometry of the American Society for Testing and Materials (ASTM) Standards E647-99. We exploited X-ray nano-diffraction (XND) mapping to characterize the crystal-deformation levels ahead of the crack tip after stress unloading under both constant- and tensile-overloaded-fatigue conditions. The crack-tip blunting-induced much higher deformation level was concentrated surrounding the crack-tip which delays the fatigue-crack growth immediately after a tensile overload. The predominant deformation texture orientation in the Paris regime was investigated, using electron backscatter diffraction (EBSD) and orientation distribution function (ODF) analyses. The twinning formation-driven shear deformation gave rise to the development of the Goss-type texture within the plastic deformation regime under a tensile-overloaded-fatigue condition, which was attributed to enhance the crack deflection and thus the tensile-induced crack-growth-retardation period in the CoCrFeMnNi HEA. Our new findings address the quantitative discrepancy found in our earlier work. Graphical abstract: Image, graphical abstract